A study on Microbial contamination and susceptibility of Hospital Theatres -at Tertiary care centre - Dr. Archana , Dr.V.Laxman Babu , Dr. Gaurav Shah (International Journal of Advanced Science and Technology, 2020)
Background: Microbial contamination of hospital environment especially the operating theatre has continued to increase the prevalence of nosocomial infection; it leads to the effect of high morbidity and mortality rate among patients admitted for surgeryAim & Objective: To study the level of contamination of air, surfaces and equipment in Operation Theatres of Osmania General Hospital - a tertiary care hospital in HyderabadMethodology: The present study was done in all operation theatres of OGH.Results: Total number of samples collected was 360, of which 120 air samples and 240 surface samples. Twenty one open plates (17.5%) were found bacterial load (TVC) above the acceptable limit. Gram positive organisms were predominant (78.33%). CoNS was the most common isolate (28.84%). Most of the Gram positive organisms were sensitive to vancomycin. Total number of Enterococci isolated were 7(1.82%), of which vancomycin resistant Enterococci were 2(0.53%). Gram negative organisms were E.coli, P.aeruginosa, Acinetobacter and Klebsiella species. All of them were sensitive to imipenem.Conclusion: Finally our study concluded that, there was a microbial contamination of hospital environment, In order to reduce it suggestions were given to the theatre personnel to reduce the foot traffic in and out of the operating rooms. And Sensitization programmes for medical, nursing and sanitary personnel every week at different timings were suggested.